brinker levels regulated by a promoter proximal element support germ cell homeostasis. - Dunipace, L.; Newcomb, S.; Stathopoulos, A. (Development, 2022)
A limited BMP signaling range in the stem cell niche of the ovary protects against germ cell tumors and promotes germ cell homeostasis. The canonical repressor of BMP signaling in both the Drosophila embryo and wing disc is the transcription factor Brinker (Brk), yet the expression and potential role of Brk in the germarium has not previously been described. Here, we find that brk expression requires a promoter-proximal element (PPE) to support long-distance enhancer action as well as to drive expression in the germarium. Furthermore, PPE subdomains have different activities; in particular, the proximal portion acts as a damper to regulate brk levels precisely. Using PPE mutants as well as tissue-specific RNA interference and overexpression, we show that altering brk expression within either the soma or the germline affects germ cell homeostasis. Remarkably, we find that Decapentaplegic (Dpp), the main BMP ligand and canonical antagonist of Brk, is upregulated by Brk in the escort cells of the germarium, demonstrating that Brk can positively regulate this pathway.